2012
DOI: 10.1073/pnas.1121622109
|View full text |Cite
|
Sign up to set email alerts
|

Conscious updating is a rhythmic process

Abstract: As the visual world changes, its representation in our consciousness must be constantly updated. Given that the external changes are continuous, it appears plausible that conscious updating is continuous as well. Alternatively, this updating could be periodic, if, for example, its implementation at the neural level relies on oscillatory activity. The flash-lag illusion, where a briefly presented flash in the vicinity of a moving object is misperceived to lag behind the moving object, is a useful tool for study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
94
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 33 publications
11
94
1
2
Order By: Relevance
“…The current study has demonstrated that oscillatory phase shapes syllable perception and that this phase difference matches temporal statistics in the environment. To determine whether this type of phase sensitization is a common neural mechanism, it is necessary to investigate other types of temporal statistics, especially because it could provide a mechanism for separating different representations (26,29,30) and offer an efficient way of coding time differences (31). Future research needs to investigate whether also other properties are encoded in phase, revealing the full potential of this type of phase coding scheme.…”
Section: Resultsmentioning
confidence: 99%
“…The current study has demonstrated that oscillatory phase shapes syllable perception and that this phase difference matches temporal statistics in the environment. To determine whether this type of phase sensitization is a common neural mechanism, it is necessary to investigate other types of temporal statistics, especially because it could provide a mechanism for separating different representations (26,29,30) and offer an efficient way of coding time differences (31). Future research needs to investigate whether also other properties are encoded in phase, revealing the full potential of this type of phase coding scheme.…”
Section: Resultsmentioning
confidence: 99%
“…EEG studies have previously tested the idea that the order of visual events was coded in the phase of the alpha oscillatory component (Gho and Varela, 1988) and recent studies have pointed out to the role of theta/alpha in temporal visual illusions (Chakravarthi and Vanrullen, 2012;VanRullen et al, 2006). These studies suggest that intrinsic oscillations are recruited for the encoding of events in the absence of external temporal regularities.…”
Section: A Canonical Role For the Phase Of Intrinsic And Entrained Nementioning
confidence: 99%
“…Under this latency code hypothesis, timing mechanisms are based on the changes of neural routing delays in sensory areas coding for a specific sensory attribute (Moutoussis and Zeki, 1997;Zeki and Bartels, 1998). To date however, electroencephalographic (EEG) studies have reported little-to-no correspondence between neural latencies and participants' perceived timing (McDonald et al, 2005;Vibell et al, 2007), and rather suggest that it is the phase of neural oscillations that plays a crucial role in the encoding of visual event timing (Chakravarthi and Vanrullen, 2012;Gho and Varela, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate compelling evidence for discrete perceptual sampling in the somatosensory domain. Using magnetoencephalography (MEG) and a tactile temporal discrimination task in humans, we find that oscillatory alphaand low beta-band (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Hz) cycles in primary somatosensory cortex represent neurophysiological correlates of discrete perceptual cycles. Our results agree with several theoretical concepts of discrete perceptual sampling and empirical evidence of perceptual cycles in the visual domain.…”
mentioning
confidence: 99%